2022
DOI: 10.1007/s12369-022-00901-1
|View full text |Cite
|
Sign up to set email alerts
|

User Profiling to Enhance Clinical Assessment and Human–Robot Interaction: A Feasibility Study

Abstract: Socially Assistive Robots (SARs) are designed to support us in our daily life as a companion, and assistance but also to support the caregivers’ work. SARs should show personalized and human-like behavior to improve their acceptance and, consequently, their use. Additionally, they should be trustworthy by caregivers and professionals to be used as support for their work (e.g. objective assessment, decision support tools). In this context the aim of the paper is dual. Firstly, this paper aims to present and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The limitations of this study were mainly related to the cohort of recruited participants. First, both cognitive and cultural backgrounds are factors that can influence the perception of emotions [52]. Some neurological pathologies (eg, Parkinson disease) can affect facial expressions, whereas others can affect body gestures and language (eg, autism spectrum disorders and apathy); consequently, emotion recognition accuracy in such cases can change.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The limitations of this study were mainly related to the cohort of recruited participants. First, both cognitive and cultural backgrounds are factors that can influence the perception of emotions [52]. Some neurological pathologies (eg, Parkinson disease) can affect facial expressions, whereas others can affect body gestures and language (eg, autism spectrum disorders and apathy); consequently, emotion recognition accuracy in such cases can change.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…For example, Lasota et al [30] indicated that even when humans reach physical safety, they can feel frustration [31] or discomfort in certain situations, and simply preventing physical contact cannot guarantee a safe and comfortable interaction between humans and robots. Thus, the evaluation of human responses is required to develop useful AMRs and socially assistive robots [32][33][34].…”
Section: Introductionmentioning
confidence: 99%